Resilience and sustainability in the informal economy: an exploration of Cape Town's informal food traders amidst disruption - Dodge, Catherine (Graduate School of Business (GSB), 2025)
The role of informal food traders in responding to the needs of local communities is crucial to achieving SDG 2: Zero Hunger. Different frameworks, developed by the Global North, have sprung up around the Sustainable Development Goals (a replacement of the Millennial Goals) to measure progress towards sustainability and address different aspects of environmental, social, and governance (ESG) but have a limited look at the role played by the informal economy. This gap highlights a lack of understanding of how informal systems contribute to sustainability, particularly in developing regions. Calls have emerged for increased research into the informal economy within a sustainability context, as previous economic models have largely ignored it. As part of this under-researched landscape, South African informal traders exemplify resilience as they face disruptions, such as rolling blackouts, extreme weather events, a global pandemic, and persistent socioeconomic challenges like high unemployment and inequality. Food security is at risk for millions of South African households as families grapple with high food inflation and low disposable incomes. Building on the strengths of inductive, interpretivist approach, this qualitative study explores how informal traders respond to disruption to increase the sustainability of their businesses in Cape Town, South Africa. Using data collected through semi-structured interviews and observations, this study sheds light on the resilience and adaptability of informal food traders and the crucial role they play in providing food security in low-income areas. It looks at existing sustainable practices within the business and highlights where technology may be used as a tool for scalability and replicability. The significance of this study lies in recognising informal traders as potential catalysts for sustainable practices, influencing larger market trends and environmental stewardship.